Study of Value Engineering Implementation Among Contractors In Malaysia - Zainal, Mazby Zubir Khairul Nazri (2008)
This project is a study or research of implementation of Value Engineering (VE) in Malaysia's construction industry focusing among the Class A to Class C contractors in Peninsular of Malaysia. The objectives of this research project are to investigate the level of awareness, implementation and the current state of VE in Malaysia's construction industry. In 2003, a research is done on this matter and it shows that the implementation is very low. There is no research done since then and it is very important to investigate the recent level of awareness and implementation in the industry because the outcome could be different from the previous research. If the no changes or the level of awareness and implementation is decreasing, the latest outcome could be used as a reference for the govern body such as Construction Industry Development Board (CIDB) to promote VE in the industry since construction industry in Malaysia contribute important element in the economy. Even it is less than 5% of the national's Gross National Product, it has extensive linkages with the rest of the economy in this country. To carry out this research, comprehensive literature review is done to provide the background and history of VE, key terminology and definitions of VE, approaches to VE in construction as well as previous study. Survey questionnaires and semi structural interviews is also used to achieve these objectives. These two methods will provide information on the awareness and perception of VE among construction professionals. From the research, it is found that the level of awareness of VE is average to high while the level of implementation is above average. Its current state of implementation is determined as widely implemented among those who implement VE. It is hope that this study will contribute as a step to establish a framework for successful implementing VE in Malaysia's construction industry.